If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(8+x)*3-1=62
We simplify the equation to the form, which is simple to understand
(8+x)*3-1=62
Reorder the terms in parentheses
(+24+3x)-1=62
Remove unnecessary parentheses
+24+3x-1=62
We move all terms containing x to the left and all other terms to the right.
+3x=+62-24+1
We simplify left and right side of the equation.
+3x=+39
We divide both sides of the equation by 3 to get x.
x=13
| 3(x-4)+7=2x+1 | | 3p-17=-7+p | | 36-25/5+3*3= | | 36-25/5+3*3=40 | | 8+x*3-1=62 | | -9s=6 | | s(t)=-16t^2+44t+4 | | 4x-2(x-4)=-5+4x+7 | | z=m^2-m(1-i)-3(2+i) | | 45x^2-7x-12=0 | | 0.006w=-0.54 | | x+1.23=65.50 | | 5t-15=2t | | 5a-3(2p+3)= | | -4.9=7m | | 14x=189-7x | | 5x+11=-59 | | 6y^2-54y=-12 | | -4x+12=-6x-36 | | 3x+2x=4x-4 | | 30=k+18 | | 4+3n-77=0 | | 208x=-4 | | 36x^2-4y^2=0 | | 2c-1=1 | | 2ln(5x)-ln(2x)=2.5 | | a-5=21 | | 5(d-15)=90 | | -8x=x^2+15 | | 8a+4-7a=3 | | p+6=28 | | y=3x^4-4X^3-12 |